Exploring cancer patients’ experiences of end-of-life care in hospital settings: A qualitative study - Mensah, Kwame; Okafor, Amina; Ndlovu, Samuel (Lentera Perawat, 2026)
Background: Cancer patients in the advanced stages of illness often receive end-of-life care in hospital settings where intensive medical interventions, complex decision-making, and limited family involvement may influence their physical, emotional, and existential experiences. Hospital-based end-of-life care presents unique challenges, particularly in contexts where palliative care integration is limited and care delivery is shaped by institutional priorities. Understanding patients’ lived experiences is essential to inform patient-centered and dignity-preserving end-of-life care practices. Objective: This study aimed to explore cancer patients’ experiences of end-of-life care in hospital settings. Methods: A qualitative phenomenological design was employed to capture the lived experiences of adult cancer patients receiving end-of-life care in hospital settings in Africa. Purposive sampling was used to recruit participants who met the inclusion criteria. Data were collected through in-depth semi-structured interviews and analyzed using thematic analysis. Strategies to ensure trustworthiness included member checking, reflexive journaling, peer debriefing, and the development of an audit trail. Results: Three main themes emerged from the analysis: experiencing physical and emotional vulnerability at the end of life, navigating relationships and communication in hospital-based end-of-life care, and seeking dignity and meaning during the final stage of life. Participants described persistent physical symptoms and emotional distress as central aspects of their end-of-life experiences. Limited communication and dependence on healthcare professionals shaped patients’ sense of control and security. Participants also emphasized the importance of dignity, respectful care, and opportunities for reflection on life and death during hospitalization. Conclusion: Cancer patients experience end-of-life care in hospital settings as a complex and deeply personal process influenced by symptom burden, communication quality, family involvement, and dignity-preserving practices. Hospital-based end-of-life care should prioritize holistic, patient-centered approaches that address physical, emotional, and existential needs.